Case Assignment in Basque - Hualde, Jose I. (Linguistica Atlantica, 1986)
This study undertakes an analysis of how ergative/absolutive Case marking takes place in Basque, in a structure which appears to be similar to that of an accusative language. Case marking of argument NP ’s is argued to occur under government by independent AGR elements which surface as agreement affixes on the auxiliary and which may occupy different structural positions in different sentences, resulting in the disparity between syntactic structure and Case marking which Basque presents. This analysis is shown to have important consequences for the analysis of impersonal and reflexive constructions, where an argument position is left unmarked for Case. Impersonal or reflexive interpretations are obtained depending on whether the subject or the object position is Caseless. The analysis also extends naturally to certain sentences which do not contain Case assigners and where the Case filter is shown to force restructuring.